1983
DOI: 10.1002/aja.1001680406
|View full text |Cite
|
Sign up to set email alerts
|

Chronobiology in hematology and immunology

Abstract: The hematopoietic and the immune systems in all their components are characterized by a multifrequency time structure with prominent rhythms in cell proliferation and cell function in the circadian, infradian, and rhythms in cell proliferation and cell function in the circadian, infradian, and circannual frequency ranges. The circulating formed elements in the peripheral blood show highly reproducible circadian rhythms. The timing and the extent of these rhythms were established in a clinically healthy human p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
117
0
3

Year Published

1985
1985
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(131 citation statements)
references
References 121 publications
10
117
0
3
Order By: Relevance
“…The hypothesis that a time-dependent effect of ASA on thromboxane production could also be at least partly responsible for the time-dependent effects of ASA on BP gains some relevancy given the lack of any effect of ASA on HR (Figure 3). Taking into account the administration timedependent BP lowering by ASA, relevant studies have also shown statistically significant circadian rhythms in thromboxane and prostacyclin production, 32 circulating platelets, 33 platelet aggregation, 32,34,35 clotting and fibrinolytic inhibitors, 32 and in the inhibition of platelet aggregation produced by ASA. 15 On the other hand, ASA has also been shown not only to restore vascular refractoriness to angiotensin II 36 but also to produce a dose-dependent BP reduction and Ͼ30% inhibition of angiotensin II.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that a time-dependent effect of ASA on thromboxane production could also be at least partly responsible for the time-dependent effects of ASA on BP gains some relevancy given the lack of any effect of ASA on HR (Figure 3). Taking into account the administration timedependent BP lowering by ASA, relevant studies have also shown statistically significant circadian rhythms in thromboxane and prostacyclin production, 32 circulating platelets, 33 platelet aggregation, 32,34,35 clotting and fibrinolytic inhibitors, 32 and in the inhibition of platelet aggregation produced by ASA. 15 On the other hand, ASA has also been shown not only to restore vascular refractoriness to angiotensin II 36 but also to produce a dose-dependent BP reduction and Ͼ30% inhibition of angiotensin II.…”
Section: Discussionmentioning
confidence: 99%
“…The number of haematopoeietic stem and progenitor cells (HSPCs) and mature leukocytes peak in the blood during the resting phase in mice [58], while levels of proinflammatory cytokines including IL-1␤ and TNF peak during the active phase [57,59]. In mice leukocytes reach their highest numbers in blood at zeitgeber time (ZT) 5 but their greatest recruitment to tissues is at ZT13 [60].…”
Section: Circadian Disruption and Diseasementioning
confidence: 99%
“…The mobilization from BM is dependent on local sympathetic innervation which down-regulates the CXCL12 expression in the BM in close association with a reduced CXCR4 expression of haematopoietic progenitors [99] and both CD4+and CD8+T cell subsets [94]. On the contrary, the onset of the active phase is related to a peak of glucocorticoids, adrenaline, noradrenaline, TNF and IL1β [95,96].…”
Section: Rhythms and Haematopoiesismentioning
confidence: 99%
“…The haematopoietic system exhibits circadian rhythms that oscillate according to the rest-activity phase that, by turn, depend on whether the species is diurnal or nocturnal. Thus, the numbers of HSCs, committed progenitor cells and most mature leukocytes, except CD8+T lymphocytes [94] peak in the circulation during the resting phase (night for humans and day for rodents) and decrease during the active period [95,96].…”
Section: Rhythms and Haematopoiesismentioning
confidence: 99%